GE_GERICHTE P/5764/2018 vom 17. Mai 2019 - GE Cour de justice (2019)
CIRCULATION ROUTIÈRE(DROIT DE LA CIRCULATION ROUTIÈRE) ; APPRÉCIATION DES PREUVES ; FIXATION DE LA PEINE ; AMENDE ; CONDAMNATION | LCR.90.al1; CPP.10.al3; CP.47; CP.106